2020
DOI: 10.1001/jamainternmed.2020.4334
|View full text |Cite
|
Sign up to set email alerts
|

Association of the National Health Guidance Intervention for Obesity and Cardiovascular Risks With Health Outcomes Among Japanese Men

Abstract: investigate the association of the national health guidance intervention in Japan with population health outcomes. DESIGN, SETTING, AND PARTICIPANTS This cohort study used a regression discontinuity design that included men aged 40 to 74 years who participated in the national health screening program in Japan from April 2013 to March 2018. EXPOSURES Assignment to the national health guidance intervention (counseling on healthy lifestyle and appropriate clinical follow-up for individuals found to have waist cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 21 publications
3
61
0
Order By: Relevance
“…The reason for stagnation in MetS prevalence in Japan is thought to be low participation in the Specific Health Guidance program. [8][9][10]12 In our study, although the questionnaire was not an established one and the data were not shown, 50% of the participants felt that it was easy to follow LOCABO, while 68% found it easier to follow it compared to other dietary approaches they had previously attempted. These findings suggest that LOCABO is a suitable method for improving participation in the Specific Health Guidance program.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The reason for stagnation in MetS prevalence in Japan is thought to be low participation in the Specific Health Guidance program. [8][9][10]12 In our study, although the questionnaire was not an established one and the data were not shown, 50% of the participants felt that it was easy to follow LOCABO, while 68% found it easier to follow it compared to other dietary approaches they had previously attempted. These findings suggest that LOCABO is a suitable method for improving participation in the Specific Health Guidance program.…”
Section: Discussionmentioning
confidence: 73%
“…9 Although preliminary evaluation studies have reported that the participants of the Specific Health Guidance program achieved body weight reduction (on average, 1.98 kg for men and 2.25 kg for women) and improvement in plasma glucose, blood pressure, and lipid profile; 10 , 11 a recent large-scale evaluation revealed no association between the Specific Health Guidance and clinically meaningful weight loss or improvement of other cardiovascular risk factors. 12 The Specific Health Guidance involves lifestyle interventions such as energy restriction and encouragement of physical activity, which are perceived as troublesome and difficult to maintain. 13 , 14 This suggests that novel methods of effective implementation are needed.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, a nationwide screening program was introduced to identify the subjects with obesity (BMI ≥ 25.0 kg/m 2 ) and risk factors of cardiovascular disease and to provide health guidance to prevent the development and progression of metabolic disorders and cardiovascular disease among the working-age population in 2008 [ 31 ]. However, Fukuma S. et al have reported that the national health guidance intervention was not associated with the reduction of cardiovascular risk such as diabetes [ 32 ]. Further research is needed to specify the subjects at high risk of metabolic disorders with or without obesity.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was reported that most subjects eligible for the guidance/intervention program did not attend the program [ 19 , 20 ], and only approximately 10% of the eligible subjects completed the program [ 21 ]. Furthermore, although the intervention program itself was shown to be sufficiently effective in eliciting behavioral modifications and improving abdominal obesity [ 19 ], a recent study reported that this intervention program was not associated with clinically meaningful weight loss or improvement of other CV risk factors [ 22 ]. Although the present study did not evaluate this particular program, our real-world results would add to these previous findings.…”
Section: Discussionmentioning
confidence: 99%